Conditionality and endogenous policy formation in a political setting - S. Mansoob Murshed (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
The paper examines two issues associated with aid and fiscal policy. First, how best the conditionality behind foreign aid, sometimes non-economic, is complied with in a principal-agent framework. In a multiple task and multiple principal framework, principals are better off cooperating and making the agent's efforts more complementary. Secondly, I examine endogenous policy formation in the context of domestic politics. This involves interaction between policy makers and domestic special interest groups. Outside donors need to be aware of these processes, so that they can ultimately influence it. I examine 3 endogenous policy processes: median voter, lobbying, and a combination of political contributions as well as altruism.
Keywords: H60; O11; O12; O19; 330; aid conditionality; fiscal policy; political processes; endogenous policy formation; Entwicklungshilfekonditionen; Finanzpolitik; Prinzipal-Agent-Theorie; Theorie; Politische Entscheidung